Advances in management accounting. Vol. 26 - Epstein, Marc J.; Malina, Mary A.; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
Volume 26 of Advances in Management Accounting examines a broad spectrum of current topics in management accounting.
Advances in Management Accounting publishes thoughtful, well-developed articles across a broad spectrum of current topics in the field of management accounting, using a variety of research methods including survey research, field tests, corporate case studies and modeling. Volume 26 exemplifies the broad scope of Advances in Management Accounting, examining a number of areas within management accounting.
Presentation formats, performance outcomes and implications for performance evaluations / Lasse Mertins, Lourdes Ferreira White -- Turnover and unit-level financial performance: an analysis of the costs and benefits of voluntary and involuntary turnover in unskilled jobs / James W. Hesford, Mary A. Malina, Mina Pizzini -- The association between the use of management accounting practices with organizational change and organizational performance / Nuraddeen Abubakar Nuhu, Kevin Baird, Ranjith Appuhami -- How management control practices enable strategic alignment during the product development process / Chris Akroyd, Sharlene Sheetal Narayan Biswas, Sharon Chuang -- Methods for cost management during product development: a review and comparison of different literatures / Marc Wouters, Susana Morales, Sven Grollmuss, Michael Scheer -- Additional evidence on the sticky behavior of costs / Chandra Subramaniam, Marcia Weidenmier Watson.
Includes bibliographical references.
Keywords: Business & Economics -- Accounting -- Managerial; Management accounting and bookkeeping; Accounting; Managerial accounting; Electronic books